Enhancement of orientation of rigid polymer blocks by incorporating rod–coil block copolymer chains into metal–organic frameworks. Issue 4 (11th February 2019) - Wang, Jin; Zhang, Yunchao; Ye, Feihong; Liu, Xiaoli; Wang, Xianlin; Zhou, Xinhui; Lu, Yunqing
Abstract: Incorporation of polymer chains into metal–organic frameworks (MOFs) is a simple yet efficient method for improving the orientation of the polymer chains. However, due to their rigidity and high molecular weight, many rigid polymer chains are either not easily loaded into MOFs, or not easily aligned within the MOF channels. In this paper, we propose a strategy for enhancing the orientation of rigid blocks by incorporating rod–coil block copolymer chains into MOFs. In this strategy, on the one hand, the rigid blocks have a low molecular weight, so that the steric hindrance effect from the MOF channels could align the rigid blocks more efficiently. On the other hand, because the covalent bonds between the repeat units of the flexible blocks can rotate relatively easily, the steric hindrance effect from the flexible blocks can further help the rigid blocks to be oriented within the MOF channels. In confirmatory simulations, two all‐atom MOF models, [Zn2 (BDC)2 (TED)] n and [Zn2 (BPDC)2 (TED)] n (TED = triethylenediamine, BDC = 1, 4‐benzenedicarboxylate, BPDC = 4, 4′‐biphenyldicarboxylate), are established. With these MOF models, molecular dynamics simulations are performed for the rigid poly(phenylene vinylene) (PPV) chain and the rod–coil block copolymer PPV‐ block ‐polystyrene (PSt). Further, their respective degrees of orientation (DoOs) are calculated. Within [Zn2 (BDC)2 (TED)] n and [Zn2 (BPDC)2 (TED)] n, the DoOs of the rigid PPV blocks of PPV‐ block ‐PSt are 0.968 and 0.902, respectively, while the DoOs of the rigid PPV chains are 0.865 and 0.711, respectively. These calculation results prove the feasibility of our proposed strategy. © 2019 Society of Chemical Industry Abstract : By incorporating a rod–coil block copolymer into a metal–organic framework (MOF) channel, the orientation of rigid blocks is enhanced via the steric hindrance effect from the MOF channel and the flexible blocks.